Effect of Dental Implant Metal Artifacts on Accuracy of Linear Measurements by Two Cone-beam Computed Tomography Systems Before and After Crown Restoration - Hoorieh Bashizadeh Fakhar; Roxana Rashtchian; Milad Parvin (Tehran University of Medical Sciences, 2017)
Objectives: The aim of this study was to determine the impact of fixture location and crown restoration on the accuracy of linear measurements by two cone-beam computed tomography (CBCT) systems. Materials and Methods: Six dental implants were inserted in a dry human mandible in two stages. CBCT images were obtained in each stage by Alphard VEGA 3030 and Promax 3D Max systems. Imaging procedures were repeated after metallic crown placement. Two observers measured the alveolar height and width using five radiopaque markers. Values were compared to the same measurements made on initial images (prior to implant insertion) using t-test. The linear regression test was used to evaluate the effect of implant location on the accuracy of linear measurements. Results: The impact of fixture and fixture-crown combination on the accuracy of linear measurements of height (t = -5.2, P=0.0001 and t=-5.98, P<0.0001, respectively) and width (t=-3.42, P=0.004 and t= -2.7, P=0.015, respectively) was significantly underestimated. Metal crowns had no significant effect on measurements of bone height and width (t=-1.38, P=0.19 and t=0, P=1.00, respectively). Although both systems showed some underestimations, Promax 3D Max underestimated bone width significantly more than the other system (Alphard VEGA 3030=- 0.51mm and Promax 3D Max=-0.80). Regarding implant location, the measurements in the canine sites were found to be more accurate than the region between adjacent implants. Conclusions: CBCT is an accurate and reproducible system for dental implant follow-up examinations. Metal artifacts can lead to underestimation of measurements. However, this was not statistically significant in our study.